Feasibility of Standardized Human Milk Collection in Neonatal Care Units - Laura Galante (Scientific Reports, 2019)
Research in human lactation is a growing field. However, difficulties in studying human milk originate from the dynamicity of its composition. Using standardized collection protocols is mandatory to minimize variation and warrant comparability of findings across different studies. Yet, information on the feasibility of collecting human milk with standardized procedures, especially in neonatal units, are lacking. The present study aims to report on the feasibility and difficulties to collect human milk according to a standardized protocol, during early lactation from women who gave birth to preterm infants. Human milk was collected from 129 mothers of moderate- to late-preterm infants according to two variations of a standard protocol which differed for number of collection time-points. Collection rates and adherence to the sampling protocol were evaluated together with reason for missed collection. Collection of ≥1 sample was successful for 80% of the mothers. However adherence to the standard protocol was overall low (36% and 27%). Collection rates were different between the two protocol variations (73% against 92%, p ≤ 0.001). Amongst the reason for missed collection, low milk supply was the most recurrent (40%). Our findings show that while collecting human milk in neonatal units is achievable, obtaining standard and comparable samples results challenging.